Evaluation of Narcotics Prescribed in Surgery, a Descriptive Study in Kabul Afghanistan, 2022 - Yassin Tawakuli; Rahim Nazari; Mohammad Rafie Rasoli; Murtaza Jafari; Friba Sultani (Zien Journals, 2022)
Pain means creating an unpleasant feeling caused by tissue injuries. Pains caused by surgery are acute pains that occur due to cuts and muscle spasms after surgery. By taking narcotic drugs, the amount of pain caused by surgery is reduced, so the prescription of narcotics in surgery is of particular importance
Keywords: surgery; narcotics; relief